Revitalisasi Pemahaman Laporan Keuangan Berbasis SAK EMKM pada UMKM Kerupuk Azizah Kota Padang - Desyani Umar; Muhammad Rivandi; Elsa Meirina; Elvirha Dwi Kartika; Hayu Yolanda Utami; Mike Kusuma Dewi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service aims to revitalize the understanding of MSME Kerupuk Azizah in Padang regarding SAK EMKM-based financial reporting to support business accountability. Post-pandemic, the partner stopped using paid applications and reverted to non-standard manual recording. The method used is participatory engagement through observation, financial education, and Cost of Goods Sold (COGS) simulation. The results showed a significant increase in understanding, with 85% of participants successfully completing a simple recording simulation. The partner actively participated in preparing Balance Sheets, Income Statements, and asset separation. This understanding becomes a foundation for preparing independent, efficient financial reports without software costs.